Husitizem na Češkem – predstopnja Lutrove reformacije - Orožen, Martina (Slavia Centralis, 2020)
Husitism in the Czech Republic – pre-stage of Luther's ReformationThe paper presents Jan Hus who questioned the authority of the Church and was thus removed from the Church scene as well as convicted at the council in Konstanz. It highlights the fact that as late as upon the 600th anniversary of his death the objective and realistic image of a man who was committed to the truth of Christ was reconstructed. He was a theologian standing up for the truth and promoting justice, a caring teacher of fellow countrymen, who were pushed to the margins of society, and a man true to his own beliefs. In his thoughts, work and life he acted responsibly and died in a deep unwavering faith according to the contents of the Second Vatican Council. The paper also highlights the controversial politicalevaluations of Hus’s personality as well as the broader religious-political situation in the Czech Republic.
Keywords: Jan Hus; Husitism; Czech Republic; Martin Luther; Reformation